It’s Time for a Change: The Role of Gibberellin in Root Meristem Development - Shtin, Margaryta; Dello Ioio, Raffaele; Del Bianco, Marta (Frontiers in Plant Science, 2022)
One of the most amazing characteristics of plants is their ability to grow and adapt their development to environmental changes. This fascinating feature is possible thanks to the activity of meristems, tissues that contain lasting self-renewal stem cells. Because of its simple and symmetric structure, the root meristem emerged as a potent system to uncover the developmental mechanisms behind the development of the meristems. The root meristem is formed during embryogenesis and sustains root growth for all the plant’s lifetime. In the last decade, gibberellins have emerged as a key regulator for root meristem development. This phytohormone functions as a molecular clock for root development. This mini review discusses the latest advances in understanding the role of gibberellin in root development and highlights the central role of this hormone as developmental timer.